2022
DOI: 10.3332/ecancer.2022.1487
|View full text |Cite
|
Sign up to set email alerts
|

Li–Fraumeni-associated pancreatic neuroendocrine tumour and XAF1 p.Glu134Ter risk modifier variant

Abstract: Studies have demonstrated that up to 17% of patients with pancreatic neuroendocrine tumours (pNETs) present pathogenic germline variants (PGVs) in several different genes, irrespective of family cancer history. Li-Fraumeni syndrome (LFS) is an autosomal dominant cancer predisposition syndrome related to PGVs in the TP53 gene. A previous case of a pNET associated with LFS (c.1009C > T, p.R337C) has been reported. Here we report the first case of a patient with pNET and TP53 p.R337H and XAF1 p.E134* germline var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(17 reference statements)
1
0
0
Order By: Relevance
“…One such example is the p.R337H founder mutation that is common throughout southern Brazil, but in the context of two haplotypes that differ in the status of XAF1 and tumor susceptibility (Hap1 and Hap2). 8 , 41 , 42 As shown here, additional non-founder independent p.R337H alleles (Hap3-5) have been identified that also likely influence cancer risk. Therefore, genetic counselors and health care providers must be aware of these distinct p.R337H haplotypes and the potential implications of their associated differences on p53 expression, structure, and function, and consequently cancer risk.…”
Section: Discussionsupporting
confidence: 58%
“…One such example is the p.R337H founder mutation that is common throughout southern Brazil, but in the context of two haplotypes that differ in the status of XAF1 and tumor susceptibility (Hap1 and Hap2). 8 , 41 , 42 As shown here, additional non-founder independent p.R337H alleles (Hap3-5) have been identified that also likely influence cancer risk. Therefore, genetic counselors and health care providers must be aware of these distinct p.R337H haplotypes and the potential implications of their associated differences on p53 expression, structure, and function, and consequently cancer risk.…”
Section: Discussionsupporting
confidence: 58%